DIGITAL TEXT: A MATERIAL PERSPECTIVE - Maria Clara Paixão de Sousa (Revista da Anpoll, 2013)
The paper suggests that digital diffusion inscribes an absolutely novel materiality for the text. Digital text is formed by the joined participation of artificial and natural logic, forming a disembodied document. “Disembodiment” is taken here as the founding conceptual property of digital texts, and it is as a determination of this property that a discussion on digital texts production and diffusion is suggested in the paper. The complete material dimension of digital texts is viewed, here, as the technological surface of a revolution in our society of knowledge.